Quality of pharmacy services and adherence to good pharmacy practice at points of sale in Punjab, Pakistan: A cross-sectional study - Jamshaid Akbar; Atif Usman; Imran Masood; Ali Hassan Gillani; Muhammad Ahmad Mahmood; Zainub Khan; Muhammad Yousif; Ali Ahmed (PLoS ONE, 2026)
Adhering to good pharmacy practice (GPP) guidelines ensures the safe, effective, and ethical delivery of pharmaceutical services at community pharmacies, commonly referred to as Point of Sale (POS). However, developing countries such as Pakistan experience poor compliance with GPP. This study aimed to evaluate the quality of pharmacy services and adherence to GPP, focusing on technology compliance, infrastructure, legal aspects, dispensing practices, storage conditions, and other essential facilities. A descriptive cross-sectional study design was employed for the current study. The sample size was determined using the online sample size calculator Raosoft TM . The method adopted for the distribution of sample among selected cities was done by proportional sampling and the convenience sampling technique was employed for accessing individual POS. A self-designed questionnaire, consisting of five sections, i.e., i) demographic data, ii) prescription recording and data management system, iii) pharmacy infrastructure, facilities and services, iv) dispensing, preparation, administration and v) distribution of medicine and storage facilities was used to gather data from the selected POS of Punjab, Pakistan between 20 th July 2024–20 th September 2024. The data were entered and analysed using IBM SPSS 23.0. Descriptive and inferential statistics were used to describe the results. A total of 598 POS were included in the final analysis. Approximately 90.6% were independent POS, with 72.7% operating in the A category. A qualified person (QP) was observed in only 29.1% of POS. Approximately 31.9% of POS did not have any computerized technology, 52.2% lacked a system for monitoring the facility’s temperature, and a significant proportion (84.6%) were involved in prescribing for minor ailments. The mean score was higher in POS operating under category A licenses, chain setups and those with one or more QP. The highest significant ( p < 0.05) mean difference observed between chain and independent POS was 3.53 (95% CI = 2.44, 4.64), between category A licensing type and no available license was 11.99 (95% CI = 8.13, 15.84), and between the presence and absence of a QP was 2.30 (95% CI = 1.58, 3.01). The findings revealed that the lack of adherence to GPP is a common practice in the country and is significantly linked to various factors such as POS type, type of license of POS, and availability and number of QP at the POS. To enhance compliance with GPP, the collaborative efforts of various stakeholders, along with targeted interventions, are essential.